2021
DOI: 10.1038/s42003-021-01882-z
|View full text |Cite
|
Sign up to set email alerts
|

Secreted midbody remnants are a class of extracellular vesicles molecularly distinct from exosomes and microparticles

Abstract: During the final stages of cell division, newly-formed daughter cells remain connected by a thin intercellular bridge containing the midbody (MB), a microtubule-rich organelle responsible for cytokinetic abscission. Following cell division the MB is asymmetrically inherited by one daughter cell where it persists as a midbody remnant (MB-R). Accumulating evidence shows MB-Rs are secreted (sMB-Rs) into the extracellular medium and engulfed by neighbouring non-sister cells. While much is known about intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(120 citation statements)
references
References 53 publications
10
110
0
Order By: Relevance
“…Transmission electron microscopy revealed that Evs were intact, spherical in morphology (Figure S2). Single particle analysis revealed that all EV samples were positive for CD9, CD81 and CD63 markers, consistent with previous reports [16,17,60,61]. All of the CD9 + , CD81 + , and CD63 + hAEC-Evs were 50-150 nm in size (Figure S3, Tables S1 and S2).…”
Section: Characterisation Of Haec-evs Reveals Media Formulation Influencing Amount Of Evssupporting
confidence: 89%
See 1 more Smart Citation
“…Transmission electron microscopy revealed that Evs were intact, spherical in morphology (Figure S2). Single particle analysis revealed that all EV samples were positive for CD9, CD81 and CD63 markers, consistent with previous reports [16,17,60,61]. All of the CD9 + , CD81 + , and CD63 + hAEC-Evs were 50-150 nm in size (Figure S3, Tables S1 and S2).…”
Section: Characterisation Of Haec-evs Reveals Media Formulation Influencing Amount Of Evssupporting
confidence: 89%
“…Importantly, EVs traffic their complex molecular cargo in a bidirectional manner, direct their cargoes to specific cell types, and upon uptake, the capacity to induce phenotypic change [13][14][15]. There is now growing awareness that predominant EV subtypes can be further stratified into distinct subtypes [6,[16][17][18].…”
mentioning
confidence: 99%
“…Extracellular vesicles (EVs) are secreted lipid-encapsulated vesicles representing an active element of the cell secretome [55]. EVs include plasma membrane-derived large EVs (termed microvesicles, 100-1500 nm size) [56][57][58][59], endosomal-derived small EVs (termed exosomes, 30-200 nm size) [58][59][60][61], midbody remnants (200-600 nm) [62,63] and exomeres (∼30 nm size) [64,65], all are well-established mediators of cancer pathology [66][67][68]. Even though exosomes and microvesicles have different biological origin, their sizes and biomarkers overlap [58,59,[69][70][71][72], as such we used the consensus MISEV guidelines to term these EVs as either large or small EVs [68].…”
Section: Significance Statementmentioning
confidence: 99%
“…Andromeda [62,[94][95][96][97]. Tandem mass spectra were searched against Homo sapiens (human) reference proteome (74,811 entries, downloaded 1-2020) supplemented with common contaminants.…”
Section: Data Processing and Bioinformatics Pipelinementioning
confidence: 99%
See 1 more Smart Citation